1989
DOI: 10.1128/jcm.27.12.2672-2677.1989
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of immunoblotting with other serological methods and virus isolation for the early detection of primary cytomegalovirus infection in allograft recipients

Abstract: Sequential specimens from nine allograft recipients were examined by using a variety of methods to detect primary cytomegalovirus (CMV) infection as rapidly as possible posttransplantation. Sera were examined for immunoglobulin G (IgG) and IgM antibodies by immunoblotting, enzyme immunoassay, and immunofluorescence and also by complement fixation, latex agglutination, and an immunofluorescence test for antibody to CMV early antigen. Urine and occasionally blood, tissue, and other specimens were centrifuged ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…The patient groups in ourstudy produced antibodies to individual CMV antigens in a pattern similar to that displayed by immunocompetent patients with natural infection. Similar observations have already been made for renal [ 13,19,271 and bone marrow transplant recipients [35] but have not been reported for heart, liver, or small bowel transplant recipients. Proteins p150, p48, and p38 were the antigens most frequently detected by IgM and IgG in primarily and recurrently infected organ transplant recipients and in immunocompetent individuals, as has already been observed in immunocompetent individuals [9,171.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The patient groups in ourstudy produced antibodies to individual CMV antigens in a pattern similar to that displayed by immunocompetent patients with natural infection. Similar observations have already been made for renal [ 13,19,271 and bone marrow transplant recipients [35] but have not been reported for heart, liver, or small bowel transplant recipients. Proteins p150, p48, and p38 were the antigens most frequently detected by IgM and IgG in primarily and recurrently infected organ transplant recipients and in immunocompetent individuals, as has already been observed in immunocompetent individuals [9,171.…”
Section: Discussionsupporting
confidence: 85%
“…Using serological methods, detection of an active infection is based mainly on significant titer rises and, therefore, requires a consecutive serum, as opposed to the detection of specific IgM, which requires only one acute phase serum. Furthermore, seroconversion to CMV in some patients precedes or coincides with virus isolation [19,22].…”
mentioning
confidence: 99%
“…In many centers, patients are monitored for laboratory evidence of CMV infection following transplantation. However, the time-consuming nature and relative lack of sensitivity of classical methods for the detection of CMV are well documented, and multiple techniques must be used for maximum efficacy of monitoring, since no single standardized test can be relied upon for the earliest possible detection of CMV infections in all patients (5). Though polymerase chain reaction technology provides rapid and sensitive detection of the presence of viral genomes (3), its usefulness as a single monitoring test has not yet been demonstrated, and its application is, in any case, restricted by high cost and technical complexity.…”
mentioning
confidence: 99%
“…Shell vial cultures of PMNLs and urine specimens were done in duplicate in human fetal lung fibroblasts as described by Smith and Espy (8), except that specimens were diluted 1:5 to avoid toxicity and staining was done at 3 days postinoculation, using the Syva Microtrak CMV Culture Identification Kit. In addition, duplicate tube cultures were inoculated and spin-amplified as described previously (5). Isolation of CMV was confirmed by IFA, using the Syva kit.…”
mentioning
confidence: 99%
“…Several review articles have reported the use of centrifugation for CMV diagnosis (106,107,265,266). The infectivity of human CMV was shown to be enhanced 8% by centrifugation of standard tube cultures at 2,000 x g for 1 h (cited in Miller et al [190]). The rapid detection of CMV by immune staining of cell cultures not centrifuged has been reported, and CMV can be detected directly in leukocytes and lavage specimens, etc.…”
Section: Centrifugationmentioning
confidence: 99%